What have the social sciences ever done for equity in health policy and health systems? - Trisha Greenhalgh (BMC, 2018)
Abstract Background The social sciences can be defined as the scientific study of human society and social relationships. Main text A number of underpinning disciplines within the social sciences, notably sociology, social psychology and anthropology, as well as interdisciplinary fields like science and technology studies and migration studies, offer both theoretical insights and methodological approaches which can productively enhance the study of equity in health systems and policy research. In particular, qualitative research in general and the use of narrative methods in particular can help illuminate individual experience and the interaction of multiple structural influences on that experience. Conclusion This article sets the theoretical scene for a special issue of the journal on social sciences and equity.